Research on Communication Technology Standard Development and Control Policy Under International Standard Competition - Chaofeng Xu; Zhanhong Xin (Dianxin kexue)
On the basis of economic interests and national security, the national economic security interests were put forward. And then a multi-stage dynamic game model was build to analyze how countries develop the new communication standard strategy and control measures, in order to protect the domestic technical standards, to maximize national security interests, when communication technology standard upgrade.